Comparison of Encased Stone Column with Conventional Column for Varied Parameters through Experimental and Numerical Investigations - Sivapriya S. V.; Jijo James; K. Pavithra; S. Renuka Devi; K. Sangeetha; M. Sasikala (Advances in Civil Engineering)
Installation of stone columns is a widely used stabilization method in improving the characteristics of soft clays. In this study, laboratory tests were conducted to understand the influence of column number, spacing and encasement on the load-carrying capacity of the modified soil. Unit cell concept is adopted for column diameters of 25.4 and 31.75 mm, one and two numbers of columns and spacings of 50, 70, and 90 mm under the conditions of with and without encasement. In addition to the laboratory study, finite element analysis was also done for similar parameters to understand the modified soil’s settlement characteristics and stress concentration ratio. Based on the analysis, it is understood that the load-carrying capacity increases with number of columns and spacing. Considering the influence of encasement, larger diameter columns showed a more significant increase in the load-carrying capacity when compared to the smaller diameter columns.